A tetrazine-fused aggregation induced emission luminogen for bioorthogonal fluorogenic bioprobe - Choi, Sang-Kee; Lee, Youngjun; Yoon, Sang Eun; Choi, Hongseo; Kim, Jonghoon; Kim, Jong H.; Lee, Sanghee; Kim, Wook; Kim, Eunha (ELSEVIER SCIENCE SA, 2021)
Bioorthogonal fluorogenic probes allow spatiotemporally controlled molecular bioimaging with minimal perturbation of the native cellular environment. Due to favorable kinetics and reaction specificity in a physiological environment, inverse electron-demand Diels - Alder reaction (iEDDA) for bioorthogonal fluorogenic bioimaging has gained immense attention in scientific field; however, the technique still needs to washout excess trans-cyclooctene labels, thereby reducing the robustness and experimental convenience. In the present study, we report tetrazine-modified aggregation-induced emission luminogens for bioorthogonal fluorogenic bioimaging. We found that a unique molecular design strategy allowed incorporation of tetrazine on aggregation-induced emission luminogens with excellent fluorogenic properties. Moreover, tetrazine modification of aggregationinduced emission luminogens results in non-radiative decay, which induces fluorescence quenching. The systematic tunability of the emission wavelength of the fluorescent core skeleton allowed successful development of three different colorful fluorogenic tetrazine-fluorophores. Furthermore, an aggregate formation study and computational calculations revealed a synergistic fluorescent quenching effect between intramolecular charge transfer and tetrazine-mediated non-radiative decay. The final simple conjugation between triphenylphosphonium and tetrazine-fluorophore enabled successful development of fluorogenic probes for spatiotemporally controlled bioorthogonal bioimaging of mitochondria in live cells with the iEDDA without washing the transcyclooctene label and tetrazine-fluorophore.
Keywords: INTRAMOLECULAR CHARGE-TRANSFER; ENERGY-TRANSFER CASSETTES; CELLULAR HETEROGENEITY; FLUORESCENCE; CYCLOADDITION; MITOCHONDRIA; MOLECULES; PROBES